Efficacy and safety of guselkumab in patients with psoriasis who have an inadequate response to ustekinumab: results of the randomized, double‐blind, phase III NAVIGATE trial. (10th October 2017) - Langley, R.G.; Tsai, T.‐F.; Flavin, S.; Song, M.; Randazzo, B.; Wasfi, Y.; Jiang, J.; Li, S.; Puig, L.
Summary: Background: Guselkumab, an anti‐interleukin‐23 monoclonal antibody, has demonstrated significant efficacy in phase III psoriasis trials. Objectives: To evaluate the efficacy and safety of guselkumab in patients with moderate‐to‐severe plaque psoriasis who had an inadequate response to ustekinumab. Methods: In this phase III, randomized, double‐blind study, 871 patients received open‐label ustekinumab (45 mg or 90 mg) at weeks 0 and 4. At week 16, 268 patients with an inadequate response to ustekinumab [Investigator's Global Assessment (IGA) ≥ 2] were randomized (double‐blind) to guselkumab 100 mg or to continue ustekinumab; 585 of 871 patients (67%) with IGA 0/1 at week 16 continued open‐label ustekinumab. The primary end point was the number of visits at which randomized patients achieved IGA 0/1 and at least a two‐grade improvement (from week 16) from week 28 to week 40. Improvement ≥ 90% or 100% in Psoriasis Area and Severity Index (PASI 90/100) and Dermatology Life Quality Index (DLQI) of 0/1 were also assessed. Results: The mean number of visits at which patients achieved IGA 0/1 and at least a two‐grade improvemen (week 28–40) was significantly greater in the guselkumab group vs. the randomized ustekinumab group (1·5 vs. 0·7; P  <   0·001); greater proportions of patients in the guselkumab group achieved IGA 0/1 and at least a two‐grade improvement at week 28 (31·1% vs. 14·3%; P  =   0·001) and week 52 (36·3% vs. 17·3%; P  <   0·001). Greater proportions of patients treated with guselkumab achieved PASI 90, PASI 100 and DLQI 0/1 at week 52. After week 16, 64·4% of patients in the guselkumab group and 55·6% in the ustekinumab group had at least one adverse event (AE); infections were the most frequent AE type. Overall, 6·7% ( n  =   9) of patients in the guselkumab group had at least one serious AE compared with 4·5% ( n  =   6) for the ustekinumab group. Conclusions: Patients treated with ustekinumab who did not achieve an IGA of 0/1 by week 16 derived significant benefit from switching to guselkumab. Abstract : What's already known about this topic? Interleukin (IL)‐23/IL‐17 is the major pathway that drives the chronic inflammation underlying the pathophysiology of psoriasis. Ustekinumab is a monoclonal antibody targeting IL‐12 and IL‐23 and is currently approved for patients with plaque psoriasis. Guselkumab is a novel anti‐IL‐23 monoclonal antibody and has demonstrated high efficacy in patients with plaque psoriasis in two recent phase III trials. What does this study add? Guselkumab demonstrated greater efficacy compared with ustekinumab among patients who failed to achieve an Investigator's Global Assessment score of 0 or 1 with ustekinumab therapy. The types of adverse events (AEs) with guselkumab and ustekinumab were similar, with infections being the most common. A slightly higher incidence of AEs was reported in the guselkumab group, primarily driven by AEs of back pain, psoriatic arthropathy and mild injection site reactions. Linked Comment:  Albrecht and Gerdes. Br J Dermatol 2018; 178 :20 . Plain language summary available online